2014
DOI: 10.1017/jfm.2014.450
|View full text |Cite
|
Sign up to set email alerts
|

A depth-averaged -rheology for shallow granular free-surface flows

Abstract: The µ(I)-rheology is a nonlinear viscous law, with a strain-rate invariant and pressure-dependent viscosity, that has proved to be effective at modelling dry granular flows in the intermediate range of the inertial number, I. This paper shows how to incorporate the rheology into depth-averaged granular avalanche models. To leading order, the rheology generates an effective basal friction, which is equivalent to a rough bed friction law. A depth-averaged viscous-like term can be derived by integrating the in-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
260
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(269 citation statements)
references
References 55 publications
7
260
0
2
Order By: Relevance
“…(21) has been carefully constructed to ensure that when it is summed over all constituents it yields the bulk incompressibility condition ∇ · u = 0. This condition and the lithostatic pressure distribution (8), are the key assumptions underlying most models for granular avalanches and geophysical mass flows (e.g., [1,20,21,30,[78][79][80][81][82][83][84]). The bulk threedimensional velocity field u may be reconstructed from depth-averaged avalanche models (e.g., [58]), or it may also be computed directly using the μ(I) rheology [85].…”
Section: Derivation Of a General Segregation Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…(21) has been carefully constructed to ensure that when it is summed over all constituents it yields the bulk incompressibility condition ∇ · u = 0. This condition and the lithostatic pressure distribution (8), are the key assumptions underlying most models for granular avalanches and geophysical mass flows (e.g., [1,20,21,30,[78][79][80][81][82][83][84]). The bulk threedimensional velocity field u may be reconstructed from depth-averaged avalanche models (e.g., [58]), or it may also be computed directly using the μ(I) rheology [85].…”
Section: Derivation Of a General Segregation Equationmentioning
confidence: 99%
“…Woodhouse et al [38] showed that this was due to ill-posedness [107] when the characteristics of the two systems coincide and strict hyperbolicity is lost. Efforts are now underway to use the μ(I)-rheology [65,85] to introduce a depth-averaged viscous term [84] into the equations to set the wavelength.…”
Section: A Depth-averaged Segregation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the Froude number is defined as Fr ¼ u= ffiffiffiffiffi gh p , where u is the slide velocity and h is the slide thickness. h was chosen as a characteristic length for the slide in analogy to MiDi (2004) and Pouliquen and Forterre (2009), as it represents the criticality of the flow, providing insight into the influence of wave speed relative to flow-speed and general flow dynamics (Gray and Edwards 2014;Heller 2011).…”
Section: Original Papermentioning
confidence: 99%
“…(3) are the gravity along the slope, the friction and the pressure gradient. The friction term can be interpreted either as a basal friction [6] or as the averaged internal friction over the thickness [17]. The friction μ(I) [4] is expressed as:…”
Section: Numerical Simulationsmentioning
confidence: 99%